Development of in situ composites via reactive friction stir processing of Ti–B4C system. (1st September 2019) - Wang, Tianhao; Gwalani, Bharat; Shukla, Shivakant; Frank, Michael; Mishra, Rajiv S.
Abstract: In situ titanium matrix composites were fabricated by introducing an exothermic reaction between Ti and B4 C during friction stir processing (FSP). Formation of TiB, TiB2, and TiC was confirmed by X-ray diffraction and transmission electron microscopy along with energy dispersive X-ray spectroscopy and diffraction pattern. TiB and TiB2 whiskers and TiC particles influenced the dynamic recrystallization process, which facilitated an equiaxed grained structure rather than the Widmanstätten microstructure. Mechanical properties of as-received Ti–6Al–4V including hardness, elastic modulus, compressive yield strength and work-hardening rate (stage B) were improved by ∼ 57%, 17%, 47% and 100%, respectively, after FSP with B4 C. Graphical abstract: Image 1